Mesquite bean and cassava leaf in diets for Nile tilapia in growth - doi: 10.4025/actascianimsci.v34i3.13175 - Monaliza Freitas Sena; Rafael Vieira de Azevedo; Ana Paula de Souza Ramos; João Sérgio Oliveira Carvalho; Leandro Batista Costa; Luis Gustavo Tavares Braga (Acta Scientiarum. Animal Sciences, 2012)
This work evaluated the inclusion of mesquite bean bran (Prosopis juliflora) and cassava leaf bran (Manihot esculenta) in diets for Nile tilapia (85.22 ± 3.13 g). Three hundred and thirty-six fish were distributed in 28 fiberglass tanks (120 L) in a 2 × 4 factorial scheme for two sources of oil and four levels of bran (0, 5, 10 and 20%) (n = 4). After 60 days, growth performance (feed intake, weight gain, apparent feed conversion and survival rate) and fish body composition were evaluated. Heights and density of villi were measured for morphometric analysis of the intestinal mucosa. Animal performance, body composition and villi density were not affected (p > 0.05) by the source and level of inclusion of bran. There was a significant effect of the level of inclusion of bran on villi height, with a linear trend, indicating that the higher the inclusion levels of bran, the lower the height of the villi. The bran studied can be used in diets for Nile tilapia up to 20% without compromising growth performance and body composition change, but the presence of these by-products can result in a deleterious effect on fish villi.